Density Based Traffic Control with Remote Override - Prakash Kumar Chaudhary; Ritik Sharma; Yuvraj Kumar Jha; S.D. Lokhande; S.S. Lokhande (International Journal of Satellite Remote Sensing, 2024)
With the burgeoning urbanization, the number of people residing in cities has been increasing since the last few decades. That implies an increase in the number of vehicles, which further leads to a calming traffic gridlock menace. Although the traditional traffic control signals are the ideal solution in this scenario, they have not proven effective due to poor time distribution. Typically, the time intervals allocated to each road are equal without considering the extent of vehicles on that road. Consequently, drivers are forced to wait a bit longer than needed. Therefore, our innovation is density-based traffic control. Thus, this system is developed to control the road traffic problems based on road density. This is accomplished by using IR sensors in order to find the density and utilizing this information, the signal timings are adjusted. Urbanization has been burgeoning these last few decades, and the number of people residing in cities has likewise expanded in tandem. More people imply more cars in which they can travel, which leads to traffic gridlock calming hazard. Traditional traffic control signals are the ideal solution in this scenario, but maintaining them has not proven effective because of time distribution. The time allocated to each of the road is traditionally allocated equally without analysing how many vehicles are on the broadcast. It forces drivers to stop more than necessary. Therefore, our innovation this time is density-based traffic control. Therefore, the system is developed to control the road traffic issues based on road density.
Keywords: Density-based-traffic; IR-sensors; RF-transmitter; emergency-vehicles; receiver